808 nm near-infrared light controlled dual-drug release and cancer therapy in vivo by upconversion mesoporous silica nanostructures. Issue 11 (1st March 2017) - Dai, Yunlu; Bi, Huiting; Deng, Xiaoran; Li, Chunxia; He, Fei; Ma, Ping'an; Yang, Piaoping; Lin, Jun
Abstract : A dual-drug co-delivery and 808 nm NIR photo-controlled release system can control drug release behaviour and enhance anticancer efficacy. Abstract : The design of stimuli-responsive drug delivery systems has attracted much attention to improve therapeutic efficacy for clinical applications. Here an 808 nm NIR light responsive dual-drug system was designed for cancer treatment both in vitro and in vivo . Mesoporous silica coated NaYF4 :Yb0.4 /Tm0.02 @NaGdF4 :Yb0.1 @NaNdF4 :Yb0.1 (UCNPs) with a core-shell structure (labeled as UCNPs@mSiO2 ) was prepared and loaded with the antitumor drug doxorubicin (DOX). The surface of the composite was functionalized with β-cyclodextrin rings bridged by the light cleavable platinum(iv ) pro-drug, thus blocking DOX inside the mesopores of silica. When excited by 808 nm NIR light, the emitted UV light from the UCNPs was used to activate the platinum(iv ) pro-drug to gain higher toxicity platinum(ii ) complexes and open the mesopores of silica (at the same time) to release DOX molecules. Both DOX and platinum(ii ) complexes can kill cancer cells. This dual-drug delivery system may represent a new avenue for the application of UCNPs in photoactivated cancer therapy.